Etiological characterizations of sporadic viral hepatitis in north east part of Bangladesh - Saha, Madhusudan; Zaki, KMJ; Chowdhury, MK Sur; Alam, Md Jahangir; Hosen, Mostafa; Safwath, Syed Alamgir; Ahmed, Mostak Uddin; Rahman, Md Oliur (Bangladesh Medical Journal, 2017)
These retrospective study was done to see common viral etiology of sporadic acute viral hepatitis in North East Part of Bangladesh. Consecutive patients attending in private chambers with acute or recent onset of jaundice with biochemical evidence of hepatocellular injury from January 2011 to December 2013 were enrolled. Epidemiological features and reports of viral markers i.e. HBsAg, Anti-HBc IgM, anti-HAV-IgM, Anti-HEV IgM, and Anti-HCV were retrieved. Data of 256 cases (male 195 and female 61, age ranging from 6 years to 89 years with mean 29.44 years were analyzed. Both HBsAg and anti-HBc-IgM were found positive in 98 (38.67%) cases (male 77 and female 21). Of them 39 were in 16-25 years age group. Anti-HAV IgM was found positive in 41 (16%) cases (male 30, female 11) and 27 of them were in the less than 16 years group. Anti HEV IgM was positive in 116 (45.31%) cases (male 87 and female 29). Majority (85 cases ) of HEV infection was found in 16 to 40 years age group. In this study HEV is the most frequent agent for acute sporadic viral hepatitis among adults followed by HBV. HAV is more prevalent cause of sporadic acute viral hepatitis among children. Bangladesh Med J. 2016 Sep; 45 (3): 138-140